Insights from an instructional team model focused on formative assessment with the support of learning researchers - Patricia Moreira; Paul Blowers; Lisa Elfring; Vicente Talanquer (Journal of Microbiology & Biology Education)
ABSTRACT Formative assessment is a key instructional practice for implementing evidence-based teaching, with research demonstrating its potential to enhance student learning. However, conducting formative assessments in large college classrooms with hundreds of students poses significant challenges, particularly in noticing, interpreting, and addressing students’ thinking in real-time. To address these challenges, we designed, implemented, and studied a specialized instructional team model (ITM) consisting of the instructor and a team of learning assistants (LAs), including a dedicated learning researcher (LR). The LR plays a central role in supporting formative assessment by collecting and interpreting evidence of student understanding in large classroom settings. Over 7 years, the ITM influenced the teaching practices of 44 instructors, 48 LRs, and 974 LAs across 21 departments and eight colleges at our institution, positively impacting the learning experiences of more than 20,000 undergraduate students. Through this work, we learned that meaningful and productive engagement in formative assessment requires long-term training for both learning assistants and instructors. This training should focus on developing their ability to elicit, notice, interpret, and respond to student thinking. These key lessons are informed by insights from three stakeholder groups: learning researchers (LRs), participating instructors, and the management team. This perspective aims to inform Science, Technology, Engineering, and Mathematics (STEM) educators and researchers interested in advancing formative assessment through the support of specialized instructional teams.